FENOMENA PENGEMIS SILVER MAN PADA USIA PRODUKTIF (Studi Kasus Di Perempatan Demangan, kab. Purworejo) - Galuh Aditya; Heru Yulianto; Bambang Widjanarko (FE Program Studi Manajemen, 2021)
This study aims to find out the phenomenon of the shift in the art of stone man to Silver Man beggar due to termination of employment due to the Covid 19 Pandemic at one of the Traffic Lights in Purworejo Regency.This study was designed to use a qualitative descriptive approach with the type of phenomenology. The sampling technique used purposive and snowball sampling. While the data collection techniques were carried out by in-depth interviews, passive observation and documentation studies. The selected sample was determined by 3 respondents and met directly at the traffic lights on the Cangkrep - Bagelen and Demangan Crossroads, Banyuurip with the criteria of productive age youth who became Silver Man beggars.Based on the results of the study, 70% of the productive age youth of the respondents chose to become silver man due to the difficulty of finding a job, being a silver man beggar allows them to share with other jobs and 30% for the reason of helping the family economy. Keywords: Silver Man Beggar, Beggar in Productive Age